Q. 84.7( 13 Votes )

Find the value of

Answer :

The given equation is: x2 +k(2x+k −1)+2 = 0


Simplifying the equation: x2 + 2kx + (k2 – k + 2) = 0


Roots of an equation are given by the formula:


x = , where, D = b2 – 4ac


For equal roots, D = 0


On comparing with ax2 + bx + c = 0, we get:


a = 1, b = 2k , c = (k2 – k + 2)


Therefore, D = 0


4k2 – 4(k2 – k + 2) = 0


4k2 – 4k2 + 4k - 8 = 0


4k – 8 = 0


4k = 8


k = 2


k = 2

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses